What Influences Visitor Mindfulness at World Heritage Sites? - Md Noor, Shuhaida; Rasoolimanesh, Mostafa S.; Jaafar, Mastura; Ganesan, Vithya (Cognizant Comm. Corp., 2015)
Mindfulness refers to a state of mind in which a person selectively and actively processes information gathered from their surrounding environment. This concept may be helpful for enhancing visitor learning at heritage sites. However, there is a paucity of literature exploring the concept of mindfulness in tourism. This study investigates the influence of both setting and visitor factors on the state of mindfulness of visitors to selected heritage sites at the Malacca World Heritage Site (WHS), Malaysia. We demonstrate that various factors correlate with visitor mindfulness, namely variety, personal connection, and the interactivity of communication media. Conversely, other visitor characteristics do not influence mindfulness directly, namely age, gender, education, nationality, and frequency of visitation. However, these features do affect the setting factors. This study contributes to the mindfulness literature regarding the importance of setting and visitor factors in a WHS and recommends that mindfulness be considered as part of an overall approach toward more sustainable heritage tourism.